Microstructural characterization and shape memory characteristics of the Ni50.3Ti34.7Hf15 shape memory alloy. (15th January 2015) - Evirgen, A.; Karaman, I.; Santamarta, R.; Pons, J.; Noebe, R.D.
Abstract: The effect of precipitation on the microstructure and shape memory characteristics of the Ni50.3 Ti34.7 Hf15 shape memory alloy has been investigated via transmission electron microscopy, differential scanning calorimetry and load-biased thermal cycling tests in tension. A one-stage martensitic transformation from B2 austenite to B19′ martensite was observed in all the aged samples but the transformation temperatures followed a more complicated trend depending on specific aging conditions. The transformation temperatures decreased below room temperature when the precipitate size, and thus the interparticle distance, was below ∼20 nm, as occurred after short aging times at low temperatures. On the other hand, the transformation temperatures can be increased over a wide temperature range by increasing the precipitate size and volume fraction through aging for long durations or at higher temperatures. The alloy demonstrated excellent dimensional stability under stress levels as high as 300 MPa as a consequence of precipitation hardening, with a maximum fully recoverable strain of 3.3% after aging at 450 °C for 10 h. The transformation thermal hysteresis also decreased in the aged samples due to reduced defect generation in the precipitation-strengthened samples. The precipitate crystal structure was identified as the H-phase that was recently reported in Ni-rich NiTiHf and NiTiZr alloys, and not the Ni4 Ti3 -type structure as reported in a few earlier studies. The H-phase present in the Ni-rich NiTiHf alloy does not change the twinning relations in the B19′ martensite phase compared to (Ti + Hf)-rich NiTiHf alloys, being a mixture of (0 0 1) compound twins and (0 1 1) Type I twins. On the other hand, the precipitates have a significant effect on martensite morphology and load-biased thermal cycling response, both of which can be manipulated by controlling the precipitate size.